Pemberdayaan Peserta Didik SMP Sekolah Master Indonesia Depok Dalam Menghadapi Perkembangan Iptek - Ery Setiyawati, Marina; Agustina S.A, Nilla; Calista Dwi, Mayla; Fakhriah, Amalia; Lativa , Dyah Ayu (Universitas Persada Indonesia YAI, 2025)
Dalam upaya mewujudkan visi